The Extraordinary Progress in Very Early Cancer Diagnosis and Personalized Therapy: The Role of Oncomarkers and Nanotechnology. (22nd March 2016) - Fruscella, Marialuigina; Ponzetto, Antonio; Crema, Annalisa; Carloni, Guido
Abstract : The impact of nanotechnology on oncology is revolutionizing cancer diagnosis and therapy and largely improving prognosis. This is mainly due to clinical translation of the most recent findings in cancer research, that is, the application of bio- and nanotechnologies. Cancer genomics and early diagnostics are increasingly playing a key role in developing more precise targeted therapies for most human tumors. In the last decade, accumulation of basic knowledge has resulted in a tremendous breakthrough in this field. Nanooncology, through the discovery of new genetic and epigenetic biomarkers, has facilitated the development of more sensitive biosensors for early cancer detection and cutting-edge multifunctionalized nanoparticles for tumor imaging and targeting. In the near future, nanooncology is expected to enable a very early tumor diagnosis, combined with personalized therapeutic approaches.